Review about Technological Systems used to detect and record heart rate in sport - José Pino Ortega; Iván Molina Carmona (Federación Extremeña de Balonmano; University of Extremadura, 2013)
Heart rate is one of the main variables used to determine the intensity of physical activity. Therefore, the analysis of heart activity during the carrying out of physical exercise has been one of the main research topics. This paper presents a review of the different technology uptake and heart rate recording currently available, as well as the different detection systems and current registration. To sum up, it is necessary to highlight that technological development has allowed generating tools of easy use so, they facilitate the registration of the intensity of physical activity and sport.